Clinical considerations of CDK4/6 inhibitors in HER2 positive breast cancer - Zhang, Cui; Zhou, Fulin; Zou, Jiali; Fang, Yanman; Liu, Yuncong; Li, Libo; Hou, Jing; Wang, Guanghui; Wang, Hua; Lai, Xiaolian; Xie, Lu; Jiang, Jia; et al. (Frontiers in Oncology, 2024)
Deregulation of cell cycles can result in a variety of cancers, including breast cancer (BC). In fact, abnormal regulation of cell cycle pathways is often observed in breast cancer, leading to malignant cell proliferation. CDK4/6 inhibitors (CDK4/6i) can block the G1 cell cycle through the cyclin D-cyclin dependent kinase 4/6-inhibitor of CDK4-retinoblastoma (cyclinD-CDK4/6-INK4-RB) pathway, thus blocking the proliferation of invasive cells, showing great therapeutic potential to inhibit the spread of BC. So far, three FDA-approved drugs have been shown to be effective in the management of advanced hormone receptor positive (HR+) BC: palbociclib, abemaciclib, and ribociclib. The combination strategy of CDK4/6i and endocrine therapy (ET) has become the standard therapeutic regimen and is increasingly applied to advanced BC patients. The present study aims to clarify whether CDK4/6i can also achieve a certain therapeutic effect on Human epidermal growth factor receptor 2 positive (HER2+) BC. Studies of CDK4/6i are not limited to patients with estrogen receptor positive/human epidermal growth factor receptor 2 negative (ER+/HER2-) advanced BC, but have also expanded to other types of BC. Several pre-clinical and clinical trials have demonstrated the potential of CDK4/6i in treating HER2+ BC. Therefore, this review summarizes the current knowledge and recent findings on the use of CDK4/6i in this type of BC, and provides ideas for the discovery of new treatment modalities.